The Magnitude of Salt Intake Behaviors and Its Predictors among Saqez Urban Population of Kurdistan District in Iran: A Cross-Sectional Study - Kolsom Khoram; Mohammad Asghari-Jafarabadi; Mehrangiz Ebrahimi-Mamagani; Behjat Shokrvash; Maral Hariri-Akbari (International Journal of Hypertension)
Background. Controlling and reducing salt intake are one of the solutions to overcome hypertension. This study aimed at determining the predictors related to salt control methods in Saqez urban population. Methods and Materials. In the present cross-sectional study, the sample population was randomly selected through cluster sampling. Data collection was performed using valid questionnaires, demographic, family economic status, knowledge, perception, intention, salt intake behaviors, and salt control methods, along with measuring body mass index (BMI) and hypertension levels. Descriptive, analytical statistical methods and multivariate logistic regression analysis were used to determine the predictors of desirable salt control methods. The variables of sex, age, family economic status, knowledge, perception, perceived social support, self-efficacy, and intention were analyzed as independent variables. Data analysis was performed using SPSS software version 24 at a significance level of 0.05. Results. Out of 766 participants, 73% were women, with mean (M) 32.83, standard deviation (SD) 9.52 years, and 77.2% were married. There were significant sex differences in employment (P=0.01) and economic status (P=0.016). The M (SD) of blood pressure (systolic/diastolic) was 110.65 (0.0212) (P=0.441). The salt intake control methods between men and women did not show significant differences (P=0.368). Among totally 88.5%, 87.7% men and 88.9% women followed desirable behaviors. The predictors that determine the adoption of salt control methods were sex (man) (OR = 0.71, 95% CI (0.38–1.29)), age (OR = 1.02, 95% CI = (0.99–1.05)), SES/FAS (medium, high level) (OR = 1.37, 95% CI = (0.754–2.47); OR = 0.46, 95% CI = (0.047–4.55)), blood pressure (OR = 1.33, 95% CI = (0.16–11.23)), knowledge (have) (OR = 1.01, 95% CI = (0.39–1.63)), intent to reduce salt (OR = 1.047, 95% CI = (1.03–1.06)), perceived salt reduction importance (OR = 1.02, 95% CI = (1.01–1.04)), perceived emotional support (health staff) (OR = 1.02, 95% CI = (1.01–1.04)), media (OR = 1.01, 95% CI = 0.99–1.02), perceived practical support (spouse) (OR = 1.02, 95% CI = 0.99–1.04)), and perceived self-efficacy (OR = 1.01, 95% CI = (0.99–1.03)). Conclusion. The support of health staff and spouse seems to be effective in controlling the salt intake behaviors of healthy individuals. In parallel with the development and change of people’s lifestyles, new approaches (legal and services) for salt control based on the support of media and social media were expected.